Disseminated intravascular coagulation developed after suction curettage in an adenomyosis patient: a case report and literature review - Xiao-Cen Niu; Li-Hua Zhu; Zhi-Da Qian; Li-Li Huang (IMR Press, 2021)
Disseminated intravascular coagulation (DIC) is a high mortality coagulopathy. The basic diseases that can induce DIC include: obstetric events, metastatic malignancy, massive trauma and bacterial sepsis. But in this article, we reported on an extremely rare case of DIC in an adenomyosis patient who had undergone suction curettage on account of unwanted pregnancy. The patient had been successfully treated with transfusion of fresh frozen plasma and subcutaneous injection of nadroparin calcium instead of hysterectomy. A decrease in progesterone, bleeding in the adenomyosis lesions, tissue necrosis, releasing of tissue factors, activating of the exogenous coagulation system might play the crucial roles in the pathophysiology of acute DIC. Since early detection and treatment are essential for the prognosis of DIC. It is suggested to strengthen the monitoring of coagulation function in such patients.